Associations of visual functions with attitudes about motor vehicle dashboards among older drivers - Swain, Thomas A.; Snyder, Scott W.; McGwin, Jr Gerald; Owsley, Cynthia (Frontiers in Neuroergonomics, 2022)
Purpose Proper understanding and interaction with the dashboard is an essential aspect of safely operating a motor vehicle. A portion of this task is dependent on vision, yet no published information exists regarding dashboard ergonomics and visual function. This study sought to associate visual functions and person abilities of dashboard ergonomic dimensions relevant to older driver design preferences and attitudes. Methods In this population-based study of drivers, participants completed functional testing for habitual distance visual acuity, contrast sensitivity, visual field sensitivity, visual processing speed, and spatial ability. A questionnaire assessed attitudes and understanding of dashboard design, with questionnaire items generated from the content of focus groups of older drivers. Dashboard design domains identified in Rasch analysis of questionnaire responses were quantified using person ability measures for the cognitive processing, lighting, obstructions, and pattern recognition domains. Visual functions and person abilities were correlated using Spearman partial correlations, adjusting for age and sex. Results A total of 997 participants completed functional testing and the dashboard questionnaire. The mean age was 77.4 ± 4.6 years, and the majority were male (55%) and white (81%). The sample had a range of person abilities and visual functions. Contrast and visual field sensitivities were significantly associated with the cognitive processing, lighting, and pattern recognition dashboard design dimensions (p ≤ 0.0052). For all significant associations, increased visual function was indicative of better person ability. Visual processing speed, as measured by Trails B and UFOV2, was significantly associated with the lighting domain (p = 0.0008 and p = 0.0007, respectively). The UFOV2 measure was correlated with pattern recognition (p = 0.0165). Spatial ability was the only visual function associated with the visual obstruction dimension (p = 0.0347). Conclusions Person ability for dashboard design domains are related to visual function in older drivers. Results show person ability for domains increased with improved visual function. Future automotive engineering and design initiatives should consider these associations in improving dashboard designs to increase vehicle utility and accessibility.